Lead Toxicity in Cereals: Mechanistic Insight Into Toxicity, Mode of Action, and Management - Aslam, Muhammad; Aslam, Ayesha; Sheraz, Muhammad; Ali, Basharat; Ulhassan, Zaid; Najeeb, Ullah; Zhou, Weijun; Gill, Rafaqat Ali (Frontiers in Plant Science, 2021)
Cereals contribute to more than 50% of total human calorie requirements worldwide. The sustainable availability of the quality cereal grains is a step forward towards resolution of high priority issue of food security. Increased concentration of heavy metals, specifically lead (Pb) in the soil adversely impact biochemical and physiological processes involved in quality grain production. The daily dietary intake of high Pb in food chain is a major concern for humans, as it can pre-dispose individuals to chronic health issues. High Pb contents cause the disruption of electron transport chain, cellular organelles integrity, membrane stability index, PSII connectivity, mineral metabolism, oxygen evolving complex and destabilization of enzymes; it further immobilizes the starch and limit nutrient availability. Plant growth promoting rhizobacteria (PGPR) is an inexpensive strategy for Pb amendment. Dark septate endophytes are found in heavy metal stressful environments. The symbiosis between endophytes and host cereal works for tolerance against Pb stress by restricting the translocation of Pb ions. Transcription factor families like bZIP, ERF and GARP as regulator explains the molecular and cellular events under Pb stress environments. There is well known role of MTP (metal tolerance protein), NRAMP (natural resistance associated macrophage protein) and heavy metal ATPase in reduction of Pb toxicity. Findings related to lead uptake, its translocation and distribution in plants would be helpful to address this problem. Reduction in Pb bioavailability in soil either by microbes, chemicals or other means, and cultivation of cultivars with low accumulation of Pb is a viable measure.